Pertumbuhan Stek Batang Sirih Merah (Piper crocatum Ruiz.) Setelah Perendaman Dengan Ekstrak Bawang Merah (Allium cepa L.) Dan Air Kelapa (Cocos nucifera L.) - Rizalinda, Nur Aprilyani Mukarlina (Jurnal Protobiont, 2018)
The Red betel (Piper crocatum Ruiz.) is one of the types of plants that can be used as a medicinal plant. The Red betel plant can be propagated through cuttings, but the ability of the Red betel leaves to stem cuttings rooted very low. The purpose of this research is to know the influence of the concentration of soaking onion extract and coconut water towards the growth of the stem cuttings of red betel. This study used a randomized complete design (RAL) factorial with two levels, namely the first factor extract of onion (B) that consists of 4 concentrations, namely control (0%), B1 (2,5%), B2 (4%), and B3 (5.5%). The second factor is cocnut water (K) consisting 0f 4 concentrations of control (0%), K1 (15%), K2 (20%) and K3 (25%), retrieved 16 combination treatments 3 replications to obtain 48 units of the experiment. The results showed that the combination of onion extract 5.5% + 25% coconut water shows most good for the number of leaves, plant height, wet weight of heading, the heading dry weight, root weight of wet and dry weight of roots.